Self-Shielding for the ZAP-X®: Revised Characterization and Evaluation - Weidlich, Georg A (Cureus, 2021)
The ZAP-X® is a newly designed, self-contained, and first-of-its-kind self-shielded therapeutic radiation therapy device dedicated to brain and head and neck stereotactic radiosurgery (SRS). By using an S-band linear accelerator (linac) and employing integrated minimal but sufficient shielding, the ZAP-X does not typically require a radiation bunker. At the same time, the self-shielded features of the ZAP-X are designed for more consistency of radiation protection, reducing the risk to radiation workers and others potentially exposed from a poorly designed or constructed radiotherapy vault. This study postulates that a radiosurgical system can be self-shielded, such that it produces radiation exposure levels deemed safe to the public while operating under a full clinical workload. The goal of self-shielding is achieved under all but the most exceptional clinical conditions. This work is intended to serve as guidance for the radiation safety evaluations of future ZAP-X treatment operations, following local or regional applicable regulatory requirements, and utilizing the unique provision of all or most of the required shielding material as an integral part of the device.